2018
DOI: 10.26773/smj.180202
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Foot Length Measurements and Body Height: A Prospective Regional Study among Adolescents in Eastern Region of Kosovo

Abstract: The purpose of this research is to examine standing height in both Kosovan genders in the Eastern Region as well as its association with foot length, as an alternative to estimating standing height. A total of 364 individuals (185 male and 179 female) participated in this research. The anthropometric measurements were taken according to the protocol of ISAK. The relationships between body height and foot length were determined using simple correlation coeffi cients at a ninety-fi ve percent confi dence interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 15 publications
0
6
0
2
Order By: Relevance
“…Based on the central and dispersion parameters, the values of skewness and kurtosis of the soccer players of FC Trepca '89, it can be stated that all the variables are within the normal distribution boundaries and that the values are very similar to those of the soccer players of FC Buducnost. It can also be stated that the soccer players of FC Trepca '89 are younger on average and that their body height is similar to the average adult body height in Kosovo (Gardasevic, 2019 ;Masanovic, Bavcevic, & Prskalo, 2019;Gardasevic, 2018;Masanovic, Gardasevic, & Arifi, 2018a;Masanovic, Gardasevic, & Arifi, 2018b;Arifi, Sermaxhaj, Gardasevic, Alaj, & Metaj, 2018;Arifi et al, 2017). It can also be concluded that almost all variables of quantitative value are better with soccer players of FC Trepca '89.…”
Section: Resultsmentioning
confidence: 85%
“…Based on the central and dispersion parameters, the values of skewness and kurtosis of the soccer players of FC Trepca '89, it can be stated that all the variables are within the normal distribution boundaries and that the values are very similar to those of the soccer players of FC Buducnost. It can also be stated that the soccer players of FC Trepca '89 are younger on average and that their body height is similar to the average adult body height in Kosovo (Gardasevic, 2019 ;Masanovic, Bavcevic, & Prskalo, 2019;Gardasevic, 2018;Masanovic, Gardasevic, & Arifi, 2018a;Masanovic, Gardasevic, & Arifi, 2018b;Arifi, Sermaxhaj, Gardasevic, Alaj, & Metaj, 2018;Arifi et al, 2017). It can also be concluded that almost all variables of quantitative value are better with soccer players of FC Trepca '89.…”
Section: Resultsmentioning
confidence: 85%
“…paralysis, fractures, amputation, scoliosis and pain). Because of these factors, an estimate of standing height has to be acquired from other reliable anthropometric indicators such as hand and tibia lengths, foot lengths, knee height, length of the forearm, length of the sternum, vertebral column length, sitting height, length of scapula, arm span as well as cranial sutures, skull, facial measurements et cetera (cited in Gardasevic, Rasidagic, Krivokapic, Corluka, & Bjelica, 2017;Popovic, 2017;Popovic, Gardasevic, Masanovic, Arifi , & Bjelica, 2017;Masanovic, Gardasevic, & Arifi , 2018a;Masanovic, Gardasevic, & Arifi , 2018b). Th erefore, all these anthropometric indicators, which are used as an alternative to estimate standing height, are very important in predicting loss in standing height connected with aging.…”
Section: Introductionmentioning
confidence: 99%
“…Može se vidjeti da u Crnoj Gori postoje varijacije kada su regioni u pitanju: sjeverna, centralana i južna regija . Interesantno je pomenuti Kosovo, jer specifi čnosti postoje u odnosu na druge populacije kada je odnos tjelesne visine i raspona ruku u pitanju, i takođe se javljaju regionalne razlike (Arifi , Bjelica, Sermaxhaj, Gardašević, Kezunović, & Popović, 2017a;Arifi , Sermaxhaj, Zejnullahu-Raçi, Alaj, & Metaj, 2017b;Mašanović, Gardašević, & Arifi , 2018d;Mašanović, Gardašević, & Arifi , 2018e;Mašanović, Gardašević, & Arifi , 2018f;Mašanović, Gardašević, & Arifi , 2018g;Mašanović, 2018;Mašanović, 2018a;. Prosječna visina Crnogoraca i Crnogorki iz Danilovgrada i Cetinja viša je od prosječne visine Litvanaca (Popović, Bjelica, & Hadžić, 2014), prosječne visine Srba (Popović, Bjelica, Molnar, Jakšić, & Akpinar, 2013), prosječne visine Islanđana (Bjelica i sar., 2012) i mnogih drugih naroda.…”
Section: Diskusijaunclassified